PEMILIHAN JENIS AIRFOIL MOHINDER UNNES MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS - Al-Janan, Dony; Gusda, Yoga (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
An UAV (Unmanned Aerial Vehicle) is an aircraft without an onboard pilot that has several functions. Mohinder is one of the fixed-wing UAVs used for mapping and monitoring areas. Currently, the Mohinder UNNES is adopted from other UAVs by reduced-scale X-UAV Talon. There are differences between dimensions and cruising speed among Mohinder and X-UAV Talon (Mohinder adaptation). The purpose of this study is to select the suitable Mohinder’s airfoil using XFLR 5 simulation using multi-criteria decision particularly the AHP (Analytical Hierarchy Process). AHP can break down the choosing into a hierarchy, compare each factor's importance, and use math to figure out the best choice based on the preferences. The selection criteria are Max Camber, Thickness α stall, Max L/Dmax, CLmax, and CL0, so then the basic airfoil shapes are AH 79-100 B, S1223 RTL, FX 63-120, dan EPPLER 395. Mohinder airfoil will be selected based on aerodynamic performance at Reynold number 200.000. The simulation results showed the AH 79-100 B airfoil has higher L/Dmax and Cl at angle of attack (AOT) -10° to 20° compared to airfoil MH-32 (Mohinder current airfoil)